Interpretive Asymmetry, Retrospective Inquiry and the Explication of Action in an Incident of Friendly Fire. Issue 4 (3rd October 2013) - Mair, Michael; Elsey, Chris; Watson, Patrick G.; Smith, Paul V.
Abstract : Video Abstract Abstract : In this article, we examine a controversial friendly fire incident that took place during the early stages of the Iraq war. Our focus is on how a cockpit video of the incident was used post facto in a military inquiry to arrive at an understanding of the actions of the pilots involved. We shall concentrate specifically on a series of interpretive difficulties that highlighted the problematic status of the video as evidence and explore what their resolution might tell us about military practice, and the place of friendly fire within it more broadly .